Causal relationship between tea intake and cardiovascular diseases: A Mendelian randomization study - Gao, Ning; Ni, Ming; Song, Jiangwei; Kong, Minjian; Wei, Dongdong; Dong, Aiqiang (Frontiers in Nutrition, 2022)
Although studies suggest that tea consumption is associated with a reduced risk of cardiovascular disease (CAD). There is no unified conclusion about the potential causal relationship between tea drinking and cardiovascular disease. We used a two-sample Mendelian randomized analysis to systematically explore the causal relationship between tea intake and cardiovascular disease subtypes for the first time. Methods: genetic tools for tea intake were identified from a ge-nome-wide association study (GWAS) involving 447,485 people. Summary data on cardio-vascular disease came from different GWAS meta-analysis studies. Inverse variance weighted (IVW) MR analysis was used as the primary method for causal analysis. A further sensitivity analysis was performed to ensure robustness of the results. Result: One standard deviation (SD) increase in tea intake was associated with a 25% (OR=0.75, 95%CI=0.61-0.91, p = 0.003) lower risk of hypertension, a 28% (OR=0.72, 95%CI=0.58-0.89, p = 0.002) lower risk of heart failure, and a 29% (OR=0.71, 95%CI=0.55-0.92, p = 0.008) lower risk of ischemic stroke, respectively. However, tea intake was not significantly associated with the risk of AF (OR=0.98, 95%CI= 0.85-1.13, p = 0.78) and CHD (OR=0.87, 95%CI=0.71-1.07, p = 0.18). Sensitivity analyses found little evidence of plei-otropy. Conclusion: Our two-sample Mendelian randomization analysis provided genetic evi-dence that tea intake was significantly associated with a reduced risk of hypertension, heart failure, and ischemic stroke. Further large randomized controlled trials should be conducted to confirm the causal effect of tea consumption on cardiovascular disease risk.